Tanda-tanda Klinis Demam Rematik - Serial Kasus - Liman, Claudia Natasha; Gozali, Ferry; Mustika, Putu Pradnyanita (Cermin Dunia Kedokteran, 2024)
Acute rheumatic fever is an autoimmune disease following group A β-hemolytic Streptococcal infection. The disease may present with variable symptoms and signs. Cases: The first case is an 8-year-old boy with arthritis and previous streptococcal infection. The treatment was glucocorticoids and antibiotics. The second case is a 17-year-old boy with prolonged fever and palpitations. Carditis was found on echocardiography. The treatment was aspirin and antibiotics. The third case is a 17-year-old girl with a congenital heart defect. The patient had severe carditis as well as arthritis. The treatment was diuretics, antibiotics, steroids, antiarrhythmics, and beta-blockers. Management differed in each case, but all had favorable outcomes. Conclusion: Clinicians should be aware of the various manifestations of rheumatic fever and come to a swift diagnosis to initiate prompt treatment, which thus can decrease disease burden and morbidity.